The boy at the door - Dahl, Alex (Head of Zeus, 2018)
"Cecilia Wilborg has it all. A loving husband, two beautiful daughters and a home in an idyllic Norwegian suburb. When the receptionist at her daughter's swim club asks her to drop off a small boy who hasn't been picked up yet, she knows it is her duty to help. When Cecilia arrives at the address she was given, the house is empty. The boy begs her to take him home with her just for the night. Cecilia reluctantly agrees but she could never guess that this little boy would soon begin to unravel her carefully constructed life and shatter everything she holds dear"--